Merancang Boneka Wayang Remaja - Junaidi Junaidi; Haryono Haryono (Institut Seni Indonesia Surakarta, 2008)
Planning the doll of adolescent puppet is creating the puppet doll especially for the adolescene. It is supposed to be a media for character education and entertainment. For the moment, puppet has been focused on the adult problems so that adolscene world has been left, consequently, we lack the adolescent appreciation toward puppet. For the reason we make a set of shadow puppet doll which is physically, suitable to the development of adolescent physic that is realistic and romantic.Keyword : puppet doll, adolescent,plan.